Atenção Primária a Saúde voltada as necessidades dos idosos: da teoria à prática - Aline Blaya Martins (Ciência & Saúde Coletiva, 2014)
This article seeks to establish a confron- tation between theory and practice with respect to healthcare for the elderly. The theory was evaluated by a study of documents that comprise the legal and theoretical framework related to the health of the elderly, which generated a matrix to assess universal access, equity, comprehensiveness and quality of care. However, the practice of healthcare was eval- uated by a population-based study conducted on 862 elderly individuals and a census that assessed primary healthcare (PHC) units in two districts of Porto Alegre in the state of Rio Grande do Sul, Brazil. The variables chosen to verify the categories were type of care accessed, first contact attribute, wheelchair accessibility and availability of priority access. Other variables include comprehensive care and the presence of dental root remains, basic PHC score, the adequacy of health facilities and ongoing professional training, as well as cross-sectional cat- egories, elderly groups and home care. A mismatch was found between recommendation and practice in some factors and advances were observed in the equity and quality of care regarding the ongoing training of professionals.